Distributed beamforming in multi-user cooperative wireless networks - Yimin Zhang; Xin Li; Amin, M. (2009 Fourth International Conference on Communications and Networking in China, 2009)
This paper considers a distributed beamformer across multiple relay nodes in a two-hop cooperative wireless network that involves multiple concurrent source-destination pairs. Each of the nodes involved in the problem, including source, relay, and destination nodes, is assumed to use a single antenna. The focus of this paper is the optimization of the relay weights that maximize the sum capacity of the wireless network. A simple solution for the determination of relay weights is provided to yield nearly optimum network capacity. Simulation results validate that, in the presence of a high number of relay nodes, the average network capacity achieved through the concurrent transmission of multiuser streams exceeds that achieved by TDMA and single-user transmission with opportunistic source selection schemes.